Conducting interviews with child victims of abuse and witnesses of crime: a practical guide - Cyr, Mireille (Routledge, 2022)
"It is a complex task to interview children who are suspected of being abused in order to gather their stories, requiring the mastery of many skills and knowledge. This book presents a synthesis of the empirical and theoretical knowledge necessary to understand the account of child victims of abuse or witnesses of crime. It is innovative by the constant links that are made between the results of the research and their significance for the interventions made to the field. It also presents in a detailed and concrete way the revised version of the National Institute of Child Health and Human Development (NICHD) Protocol, a forensic structured interview guide empirically supported by numerous studies carried out in different countries. The step-by-step explanations are illustrated with the verbatim of an interview with a child as well as other tools to help the interviewer to prepare and handle an efficient and supportive interview. This book is intended for stakeholders in the justice, social and health systems as well as anyone likely to receive allegations from children (e.g. educators, daycare staff). Although the NICHD-R Protocol is intended to forensic interviewers, the science behind its development and application is relevant to all professionals who worked with children. This book is intended to be a practical and thoughtful guide for the forensic interview of children"--